Nursing leaders' perceptions of the impact of the Strengths-Based Nursing and Healthcare Leadership program three months post training - Mélanie Lavoie-Tremblay; Kathleen Boies; Christina Clausen; Julie Frechette; Kimberley Manning; Christina Gelsomini; Guylaine Cyr; Geneviève Lavigne; Bruce Gottlieb; Laurie N. Gottlieb (Elsevier, 2024)
Background: Development of nursing leadership is necessary to ensure that nurse leaders of the future are well-equipped to tackle the challenges of a burdened healthcare system. In this context, the Strengths-Based Nursing and Healthcare Leadership program was delivered to 121 participants from 5 organizations in Canada in 2021 and 2022. To date, no study used a qualitative approach to explore nursing leaders' perceptions of a leadership Strengths-Based Nursing and Healthcare Leadership program three months post training. Objective: To describe nursing leaders' perceptions of the impact of the Strengths-Based Nursing and Healthcare Leadership program three months post training. Methods: Qualitative descriptive design was used with individual semi-structured interviews. A convenient sample of nurse leaders (n = 20) who had participated in the leadership program were recruited for an individual interview three months post training. The data generated by interviews were analyzed using a method of thematic content analysis. Results: Three themes emerged from the qualitative data analysis related to the leadership program that stayed with participants three months post training: 1) mentorship: a lasting relationship, 2) human connections through Story-sharing, and 3) focus on strengths. Two other themes emerged related to the changes that they have made since attending the program: 1) seeking out different perspectives to work better as a team and 2) create a positive work environment and to show appreciation for their staff. Conclusion: The present study offers evidence of the impact of the Strengths-Based Nursing and Healthcare Leadership program three months post training. Implication: This study reinforces the importance of training using a Strengths-Based Nursing and Healthcare Leadership lens when tackling leadership.